Risk stratification strategy and assessment of disease progression in patients with pulmonary arterial hypertension: Updated Recommendations from the Cologne Consensus Conference 2018. (1st December 2018) - Leuchte, Hanno H.; ten Freyhaus, Henrik; Gall, Henning; Halank, Michael; Hoeper, Marius M.; Kaemmerer, Harald; Kähler, Christian; Riemekasten, Gabriela; Ulrich, Silvia; Schwaiblmair, Martin; Ewert, Ralf
Abstract: In the summer of 2016, delegates from the German Respiratory Society, the German Society of Cardiology and the German Society of Pediatric Cardiology met in Cologne, Germany, to define consensus-based practice recommendations for the management of patients with pulmonary arterial hypertension (PAH). These recommendations were built on the 2015 European Pulmonary Hypertension guidelines and included new evidence, where available, and were last updated in the spring of 2018. This article focusses on the proposed risk stratification and assessment of disease progression in patients with pulmonary arterial hypertension (PAH), covering 3 parts: In part 1, methods and markers that are recommended to assess severity and progression of PAH are discussed and commented. These updated comments incorporate most recent data as well as challenges arising from the variability of phenotypes of PAH patients with increasing cardiopulmonary comorbidities. In part 2, the proposed ESC/ERS risk stratification strategy is discussed, together with a review of the recent validation studies from different European registries. Finally, in part 3, the working group of the Cologne Consensus Conference provides recommendations on how risk assessment may be implemented in routine clinical practice and may serve clinical decision making.